2004
DOI: 10.1021/es040400c
|View full text |Cite
|
Sign up to set email alerts
|

Initial Public Perceptions of Deep Geological and Oceanic Disposal of Carbon Dioxide

Abstract: Two studies were conducted to gauge likely public perceptions of proposals to avoid releasing carbon dioxide from power plants to the atmosphere by injecting it into deep geological formations or the deep ocean. Following a modified version of the mental model interview method, Study 1 involved face-to-face interviews with 18 nontechnical respondents. Respondents shared their beliefs after receiving basic information about the technologies and again after getting specific details. Many interviewees wanted to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
117
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(126 citation statements)
references
References 18 publications
(32 reference statements)
8
117
1
Order By: Relevance
“…Results indicated that, at baseline, participants' feelings about CCS were slightly positive, while their perceived knowledge was relatively low, which replicates findings of previous CCS studies (Huijts et al, 2007;Palmgren et al, 2004;Shackley et al, 2005;Sharp et al, 2009;Wallquist et al, 2009Wallquist et al, , 2010 We found support for Hypothesis 1, which predicted that responses to educational materials about CCS would be informed by prior feelings about CCS. Table 1 shows a significant correlation between post-education feelings about CCS and baseline feelings about CCS.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Results indicated that, at baseline, participants' feelings about CCS were slightly positive, while their perceived knowledge was relatively low, which replicates findings of previous CCS studies (Huijts et al, 2007;Palmgren et al, 2004;Shackley et al, 2005;Sharp et al, 2009;Wallquist et al, 2009Wallquist et al, , 2010 We found support for Hypothesis 1, which predicted that responses to educational materials about CCS would be informed by prior feelings about CCS. Table 1 shows a significant correlation between post-education feelings about CCS and baseline feelings about CCS.…”
Section: Resultssupporting
confidence: 85%
“…As in Study 1, a one-sided t-test found that baseline feelings about CCS as reported across participants were slightly positive, with a one-sided t-test showing that the mean rating was significantly above the scale midpoint of 4 (M=4.51, SD=1.24), t(319)=7.31, p<.001, thus falling in the range of previous public perception studies, which have reported ratings that vary from slightly negative to slightly positive (Huijts et al, 2007;Palmgren et al, 2004;Shackley et al, 2005;Sharp et al, 2009;Wallquist et al, 2009Wallquist et al, , 2010. Because the baseline assessment occurred before participants received the one-sided argument, baseline feelings about CCS should show no significant difference between participants who were to receive the pro-CCS argument and those who were to receive the anti-CCS argument, as is indeed the case (Table 3).…”
Section: Initial Analysesmentioning
confidence: 64%
See 3 more Smart Citations